2017
DOI: 10.1021/acs.nanolett.7b03179
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Halide Perovskites with Stabilized Bandgaps

Abstract: One merit of organic-inorganic hybrid perovskites is their tunable bandgap by adjusting the halide stoichiometry, an aspect critical to their application in tandem solar cells, wavelength-tunable light emitting diodes (LEDs), and lasers. However, the phase separation of mixed-halide perovskites caused by light or applied bias results in undesirable recombination at iodide-rich domains, meaning open-circuit voltage (V) pinning in solar cells and infrared emission in LEDs. Here, we report an approach to suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
215
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(219 citation statements)
references
References 29 publications
3
215
1
Order By: Relevance
“…The photo‐induced halide segregation seriously damages the device performance, leads to open‐circuit voltage ( V oc ) decrease and photo‐induced traps. It is demonstrated that the photo‐induced halide segregation is affected by lattice strain, traps, light intensity, pressure, or compositional uniformity, but the origin is still unclear . Since the halide segregation is as the result of ion migration, therefore, it can be suppressed by increasing the ion migration barrier.…”
Section: Materials Stabilitymentioning
confidence: 99%
“…The photo‐induced halide segregation seriously damages the device performance, leads to open‐circuit voltage ( V oc ) decrease and photo‐induced traps. It is demonstrated that the photo‐induced halide segregation is affected by lattice strain, traps, light intensity, pressure, or compositional uniformity, but the origin is still unclear . Since the halide segregation is as the result of ion migration, therefore, it can be suppressed by increasing the ion migration barrier.…”
Section: Materials Stabilitymentioning
confidence: 99%
“…Besides their sensitivity to moisture, oxygen, light, electric field, or thermal stress, an existing self-degradation pathway [26,27] is also a big issue in hybrid organic-inorganic lead halide perovskites. [28][29][30][31][32] The group IV elements, tin (Sn) [23,[33][34][35] and germanium (Ge), [34,36] have been employed as the replacements for Pb. [28][29][30][31][32] The group IV elements, tin (Sn) [23,[33][34][35] and germanium (Ge), [34,36] have been employed as the replacements for Pb.…”
mentioning
confidence: 99%
“…Rand and co-workers found that, with the percentage of loadings of butylammonium (BA) no more than 20 mol% as compared to the molar amount of the 3D perovskites, the bulky BA cations only play the role of surface ligands that confines the growth rather than participate in the crystallization of the PNC grains. [55,88] Similarly, 3D PNCs of MAPbI 3 and MAPbBr 3 with 5.4 and 6.4 nm in size were also realized at an incorporation molar ratio of 20% with fluorophenylmethylammonium (FPMA) and PEA, respectively (Figure 5b). [89] At higher incorporation amount, however, multilayered RP phases begin to appear with the large OA cations intercalate into the crystal For the excess MABr case, a type I structure was formed with larger bandgap MABr (4.0 eV) and a smaller one for MAPbBr 3 (≈2.2 eV).…”
Section: Organic Ammonium Assisted In Situ Fabricationmentioning
confidence: 89%
“…Reproduced with permission. [17,51,53,59,67,78,88] Copyright 2014-2017, American Chemical Society; [57] Copyright 2015, American Association for the Advancement of Science; [58] Copyright 2012, The Chemical Society of Japan; [63,65] Copyright 2016, Springer Nature; [62,[70][71][72]117,121] Copyright 2015-2018, Wiley-VCH. mesostructured films through sol-gel treatment of TiO 2 and SiO 2 precursors within organic templating agents.…”
Section: Hard Template Assisted In Situ Fabricationmentioning
confidence: 99%
See 1 more Smart Citation